Initial Observation of a Large Proportion of Patients Presenting with Clinical Stage T1 Renal Masses: Results from the MUSIC-KIDNEY Statewide Collaborative - Amit K. Patel; Craig G. Rogers; Anna Johnson; Sabrina L. Noyes; Ji Qi; David Miller; Edward Shervish; Benjamin Stockton; Brian R. Lane (European Urology Open Science, 2021)
Background: While surgical excision remains the principal management strategy for clinical T1 renal masses (cT1RMs), the rates of noninterventional approaches are not well known. Most single-institution and population-based series suggest rates below 10%. Objective: To evaluate the use of observation for newly diagnosed cT1RM patients in academic and community-based practices across a statewide collaborative. Design, setting, and participants: The Michigan Urological Surgery Improvement Collaborative—Kidney mass: Identifying and Defining Necessary Evaluation and therapY (MUSIC-KIDNEY) commenced data collection in September 2017 by recording clinical, radiographic, pathologic, and short-term follow-up data for cT1RM patients at 13 diverse practices. Patients with complete data were assessed at >90 d after initial evaluation as to whether observation or treatment was performed. Outcome measurements and statistical analysis: Relationships with outcomes were analyzed using multivariable logistic regression, chi-square test, and Wilcoxon rank-sum test. Results and limitations: Out of 965 patients, observation was employed in 48% (n = 459), with practice-level rates ranging from 0% to 68%. Patients managed with observation (vs treatment) were significantly older (71.2 vs 62.8 yr, p <  0.0001) and had smaller tumors (2.3 vs 3.4 cm, p <  0.0001). Observation was used for 53.5% of cT1a renal masses, for 29.9% of cT1b renal masses, and for 42.5%, 53.7%, and 63.9% of radiographically solid, Bosniak III–IV cystic, and indeterminate cT1RMs, respectively. Factors significantly associated with observation in multivariable analysis included lesion type (Bosniak III–IV vs solid, p =  0.017), tumor stage (cT1a vs cT1b, p <  0.001), and higher age (p <  0.001). A short duration of follow-up limits the assessment of longer-term patient management. Conclusions: Noninterventional management of cT1RMs is common across the MUSIC-KIDNEY collaborative, with wide variability across practices. Factors associated with observation were advanced age, smaller tumor size, and cystic tumor type. Durability of the initial decision for observation (delayed intervention vs active surveillance vs less active surveillance) will be a focus of subsequent study. Patient summary: The Michigan Urological Surgery Improvement Collaborative: Kidney mass: Identifying and Defining Necessary Evaluation and therapY (MUSIC-KIDNEY) quality improvement collaborative assessed the current utilization of initial observation of a renal mass ≤7 cm across a diverse group of urology practices and found it to be used in 48% of patients. We found that the factors predicting observation were advanced age, smaller tumor size, and cystic tumor type.